2008
DOI: 10.1177/0363546508324694
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Repair of the Lacertus Fibrosus on Distal Biceps Tendon Repairs

Abstract: Repair of the lacertus fibrosus as an adjunct to distal biceps tendon repair strengthens the repair in the laboratory setting. Clinical testing is needed to verify that this increased strength improves clinical results. Surgeons should be cautioned to protect the underlying neurovascular structures during repair of the lacertus fibrosus and to avoid an overly tight repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…Nerve complications were avoided. Consistent with the literature [8][9][10][11][12], which shows no differences in the use of allogeneic versus autologous grafts, ultrasonography and also MRI showed normal healing of the allogeneic graft in our case. The postoperative result after 3 months tallies with the results reported in the literature with evidence of full mobility and no subjective deficit in power.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nerve complications were avoided. Consistent with the literature [8][9][10][11][12], which shows no differences in the use of allogeneic versus autologous grafts, ultrasonography and also MRI showed normal healing of the allogeneic graft in our case. The postoperative result after 3 months tallies with the results reported in the literature with evidence of full mobility and no subjective deficit in power.…”
Section: Discussionsupporting
confidence: 92%
“…Using fresh-frozen comparison groups, Landa et al [11] studied biomechanically the additional augmentation of the reattached distal biceps tendon with the lacertus fibrosus compared with a group without augmentation. They showed that the tear strength was greater in the augmentation group although there was no difference in stiffness.…”
Section: Resultsmentioning
confidence: 99%
“…Si se encuentra indemne, puede minimizar la retracción del tendón, ayudando a estabilizar la porción corta y limitar el déficit funcional en pacientes de baja demanda funcional (8) . La necesidad de repararlo cuando se produce una rotura asociada con la del tendón es muy controvertida y pocos autores la recomiendan por el potencial de producir un compromiso de las estructuras neurovasculares que discurren dorsalmente (16) . En los casos de roturas crónicas con lesión asociada del lacerto parece que permite una mayor retracción del tendón del bíceps y es más probable tener que recurrir al uso de injertos tendinosos (17,18) .…”
Section: Anatomía Y Conceptos Biomecánicos Del Tendón Y La Tuberosidaunclassified
“…2 The need to preserve an intact lacertus fibrosus or even repair the lacertus at the time of surgery is very controversial. 14 If the lacertus fibrosus is repaired, it should be done in forearm pronation and extension to minimise the risk of impingement on adjacent neurovascular structures. 7,15 If the lacertus fibrosus is intact in a chronic tear, it usually prevents the proximal migration of the tendon, and may make tendon repair easier.…”
Section: Relevant Anatomymentioning
confidence: 99%